Kehidupan Berkelompok Remaja di Kenagarian Lagan Hilir Punggasan Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan - Apandi, Irvan; Sano, Afrizal; Nofrita, Nofrita (Bimbingan dan Konseling, 2014)
Social relationship in group teenagers of life see about there accept and refuse teenagers in group, teenagers that is accepted in groups able to want joinning, have responsibility and many ideas to solve the problems in group. Teenagers that is refused in group have arrogant oneself, do not work together in groups, commanding, and like arrange the others and also least wise. The purpose of this research is to know and describe: 1) Conception of group teenager living is seen from accepting the friends, 2) Conception of group teenager living is looked from refusing the friends.This research is Qualitative Descriptive Research. The population of the research is all of teenagers at Kenagarian Lagan Hilir Punggasan Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan sum 58 person. The ways of taking sample in this research use Total Sampling which is all of population is became sample. The sources in this research is primer and sekunder data sources. The technique of data collection of the research uses questionaires that is given for teenagers. The data of this research is calculated using percentage formula.The result of the research expresses that group teenagers life at Kenagarian Lagan Hilir Punggasan Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan in category very good 51,72% and accepting the friends in category good 67,24% and also style of indicator is very good 84,48%, action is very good 44,83%, have inisiatif is good 43,1%, attitude is very good 63,79%, feeling is very good 53,45%,Â  honest and responsibility are good 36,2%, joinning is good 24,14 %. Furthermore, in refusing of friends are very good 74,14% and indicators often oppose norm and valueÂ  that are very good 84,73% and also far house from group of friends are very good 65,52%.Â